Desenvolvimento e aplicação de um modelo de sustentabilidade baseado no sistema de gestão ambiental implementado de uma instituição de ensino superior brasileira - Dai-Prá, Léa Beatriz (Universidade do Vale do Rio dos Sinos, 2023)
Higher Education Institutions (HEIs) play a relevant role in the education of the academic community and of the society to which they are inserted. As the concepts of sustainability emerged, many Universities also started their journey in sustainable development, managing their institutions environmentally, socially, and economically. To monitor and measure the Environmental Management Systems (EMS) of institutions, there are several tools and metrics, among them, certifications, which undergo auditing processes; and there are models developed with the objective of measuring sustainability, considering the particularities of the university and its environmental management. In this context, the main objective of this work was to develop and apply a sustainability model, based on existing EMS data from a Brazilian HEI, ISO 14001 certified, the Universidade do Vale do Rio dos Sinos (UNISINOS). The two university campuses (Unisinos São Leopoldo and Unisinos Porto Alegre) were used as case studies for the adoption of the model. Methodologically, four steps were used to achieve the main objective of this thesis: 1) analysis of UNISINOS EMS indicators (environmental, social and economic) from start (São Leopoldo – 2004; Porto Alegre - 2019); 2) conducting an online questionnaire applied to the academic community; 3) development of the model with its parameters and scores (using data from 2017 to 2022); 4) comparison between campuses and critical analysis of Unisinos' sustainability (based on previous steps). The indicator analysis stage showed that UNISINOS EMS has been applying monthly monitoring and working on improvements to its system since it started, including environmental education for the academic community. In the online questionnaire, the feedback from the community pointed mainly to the good development of the University's environmental management, in addition to indicating the concern with environmental awareness and the existence of environmental indicators. In the development of the model, Unisinos São Leopoldo, which has had the EMS for the longest time, evolved around 33 points, from 2017 to 2022, on the sustainability scale created, going from 'Sustainable medium level' to 'Sustainable ' in the model evaluation. And Unisinos Porto Alegre, with the most recent EMS, still has many fluctuations between the years studied (2019-2022), about 39 points of difference in the sustainability scale from 2019 to 2022, with an evaluation of 'Sustainable medium level' in the last year evaluated, requiring more attention and monitoring time to be fully evaluated, but despite this, it has shown good results in environmental indicators, for example . The period of the COVID-19 pandemic brought many uncertainties to the world and, consequently, to sustainable development, which was largely harmed, since attention was focused mainly on the health of the population and survival, pausing the development of several sectors, such as economic and environmental. Unisinos also suffered from this event and there was a setback in the evolution of the sustainability of both campuses, in the indicator’s evolution, which are now working on their recovery. Finally, the conclusion of this work is that the University must keep its strategies aligned, be they environmental, economic, or social management. All spheres of sustainability must be in order, for the sustainable development of the institution to succeed.
Keywords: Modelo de sustentabilidade; Sustentabilidade em universidades; Gestão Ambiental; SGA UNISINOS; UNISINOS; Sustainability model; Sustainability in universities; Environmental management; UNISINOS EMS; ACCNPQ::Engenharias::Engenharia Civil